Diagnostic Yield of Next-Generation Sequencing for Rare Pediatric Genetic Disorders: A Single-Center Experience - Milena Stoyanova; Dinnar Yahya; Mari Hachmeriyan; Mariya Levkova (Medical Sciences, 2025)
Background: Next-generation sequencing (NGS), particularly whole-exome sequencing (WES), has become a powerful diagnostic tool for rare genetic conditions. However, its success rate varies based on the underlying genetic etiology and the population studied. Methods: This retrospective study evaluated the diagnostic yield of NGS in a cohort of 137 pediatric patients with suspected rare genetic disorders in Bulgaria, a setting where such testing is not reimbursed and must be self-funded. The patients underwent either WES or targeted gene panel testing based on clinical presentation, family history, and genetic evaluation. Results: The overall diagnostic yield was 45.99%, with WES achieving 51.25% and targeted testing achieving 38.60%. The highest yield was observed in patients presenting with both dysmorphic features and neurodevelopmental delays (62.5%), while the lowest was observed among those with isolated neurodevelopmental issues (10%). A significant portion of the identified variants (35.9%) were novel. Eight patients were diagnosed with copy number variants (CNVs) detected only through WES. Conclusions: Our findings illustrate the value of WES as a first-line test and highlight the impact of deep phenotyping on diagnostic success. This study also emphasizes the need for a population-specific reference genome and equal access to genomic diagnostics in all European countries.